Dynamic Performance Investigations of a Full-Scale Unanchored Thin-Walled Steel Fluid Storage Tank via Shake Table Tests - Hosseini, Ehsan; Beskhyroun, Sherif (My University, 2024)
Theoretical models proposed in the literature and seismic design codes make the basis of analysis and the design procedures of fluid storage tanks. These models are derived based on many simplified and approximate assumptions. Under realistic conditions, however, different factors cause violation of these assumptions, causing the fluid flow and fluid–structure interaction (FSI) to diverge from theories. In this research work, 38 swept-sine tests and 63 seismic ground motions were applied to a full-scale highly flexible unanchored thin-walled stainless steel fluid tank. The experimental natural frequencies of the system for three different aspect ratios of 2.1, 2.8, and 3.5 were calculated and compared with the theoretical ones. Damping ratios for different modes were calculated using the half-power bandwidth analysis. Experimental results revealed discrepancies between the theoretical and experimentally detected natural frequencies, especially for the convective mode. Closer matches were found for the aspect ratios of 2.8 and 3.5, for the impulsive mode. Acceleration amplification factors at different heights of the shell were calculated which showed a nonlinear behaviour with a descending trend from the base to the mid-height and then an ascending one towards the fluid surface. Maximum acceleration amplification factor occurred at the surface of the fluid. The axial strains around the base are maximum and decrease bi-linearly towards the upper heights of the shell. Effects of the input excitation frequency content over the structural responses of the system were examined. Frequency characteristics of the input excitation considerably affected the maximum acceleration amplification factors and axial strains in the shell.
Keywords: 0905 Civil Engineering; 1202 Building; 4005 Civil engineering